Creativity and the future of engineering education: making the strange familiar - Ahmad, Zuraida; Halim, Zahurin (2013)
Universities are increasingly expected to provide more opportunities that foster and nurture creativity in engineering students. It is an ongoing critical issue, in the sense that it helps, meets the expectation for professional engineers, as well ad completes the intellectual development of individuals. The importance of implementing creativity education in the lecture however has not been fully recognised and implemented. Therefore. this paper is trying to examines the meaning of creativity and the technique (teaching pedagogy) that can be implemented in teaching it to engineering students without burdening them with extra workload. In doing so, the authors are reporting the trial technique of nurturing creativity in the classroom during the lecture and offer strategies to make creativity a part of engineering curriculum.